Strengthening Reading Mastery through Course Review Horey in Elementary Students: Penguatan Kemampuan Membaca Melalui Course Review Horey pada Siswa Sekolah Dasar - Rara; Apdoludin; Reni Guswita (Academia Open, 2025)
Background: Education is a key driver in shaping students’ knowledge and character, with Indonesian language literacy being crucial at the elementary level. Specific Background: Many fifth-grade students at SDN 224/II Sijau struggled with reading comprehension and failed to meet the Minimum Completion Criteria, showing low motivation and participation. Knowledge Gap: Although the Course Review Horey (CRH) model has been studied, few works explicitly examined its structured use in improving reading comprehension for low-participation students. Aims: This study aimed to describe how CRH could strengthen reading comprehension and participation in Indonesian language lessons. Results: Through two cycles of classroom action research, teacher performance improved (82.5% to 92.5%), student engagement increased (68.5% to 90.6%), and mastery learning rose from 62.5% to 94%. Novelty: The research applied CRH systematically across two action cycles, creating a lively, game-like, student-centered environment. Implications: Findings suggest CRH can be adopted widely to support literacy development and active participation in elementary language learning. Highlight: Students’ reading comprehension improved significantly after two CRH cycles Teachers became more skilled at managing interactive, student-centered lessons CRH fostered engagement, motivation, and better learning atmosphere Keywords: Course Review Horey, Reading Comprehension, Student Participation, Elementary Education, Classroom Action Research